Appraising the Local Village Leaders‘ Response to the Challenges Faced by Rural Households during the Corona Virus 2019 National Lock-down in South Africa - Amaechi, K Ekene; Iwara, Ishmael Obaeko; Musvipwa, Faith; Raselekaone, Raymond (Sociološki pregled, 2022)
This study investigates Tswinga village local leaders‘ efforts in responding to COVID-19 pandemic challenges grappling its households. It draws from ideas in Afrocentrism to evaluate local community leaders‘ response to the pandemic during the first 65 days of the South African COVID-19 lockdown. Data were collected through semi-structured interviews of both local leaders of the village and the local Municipality‘s COVID-19 response team. The study found that no significant progress in the fight against the COVID-19 would have been made if the national strategy to combat the virus had not been adapted to the local situation by local leadership. Hence, the study recommends a comprehensive multi-stakeholder involvement and a bottom-up approach when developing strategies to curb the pandemic to ensure that the strategy responds to the varying dynamics prevailing in different regions of the country.